Sharia Hotel Business Development in North Sumatera Province: Challenges and Strategies from an Islamic Perspective - Haddad Ulum Harahap; Rijal Allamah Harahap (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This study aims to identify the main obstacles faced by Istana IV Syariah Hotel in business development and to formulate appropriate solutions and strategic priorities. The study employed the Analytic Network Process (ANP) using Super Decisions software. Data were collected through pairwise comparison questionnaires administered to respondents consisting of sharia hotel experts and practitioners. The findings indicate that internal factors represent the primary challenge in developing the sharia hotel business, followed by external factors. Human resource issues and sharia hotel management emerged as the most significant internal constraints, while time-related factors and regulatory policies were identified as the main external challenges. The priority solutions emphasize strengthening internal capacity, particularly through improving human resources and management practices. The strategic priorities focus on enhancing competitiveness without engaging in price wars, targeting appropriate market segments, improving service quality and customer experience, strengthening partnerships with travel aggregators, and optimizing digital marketing through social media, email marketing, retargeting, and content development. These findings provide practical guidance for improving the competitiveness and sustainable development of sharia hotels in North Sumatra. Penelitian ini bertujuan untuk mengidentifikasi kendala utama yang dihadapi Hotel Istana IV Syariah dalam pengembangan usaha serta merumuskan solusi dan prioritas strategi yang tepat. Penelitian ini menggunakan metode Analytic Network Process (ANP) dengan bantuan perangkat lunak Super Decisions. Data diperoleh melalui kuesioner perbandingan berpasangan yang diberikan kepada responden yang terdiri atas pakar dan praktisi perhotelan syariah. Hasil penelitian menunjukkan bahwa faktor internal merupakan kendala utama dalam pengembangan bisnis hotel syariah, diikuti oleh faktor eksternal. Permasalahan sumber daya manusia dan manajemen hotel syariah menjadi kendala internal yang paling dominan, sedangkan keterbatasan waktu dan kebijakan regulasi merupakan kendala eksternal yang paling penting. Solusi yang diprioritaskan berfokus pada penguatan kapasitas internal, terutama melalui peningkatan kualitas sumber daya manusia dan pengelolaan hotel. Adapun strategi utama yang direkomendasikan meliputi peningkatan daya saing tanpa melakukan perang harga, penentuan segmen pasar yang tepat, peningkatan kualitas layanan dan pengalaman pelanggan, penguatan kerja sama dengan agregator perjalanan, serta optimalisasi pemasaran digital melalui media sosial, email marketing, retargeting, dan pengembangan konten. Temuan ini memberikan rekomendasi praktis bagi peningkatan daya saing dan pengembangan hotel syariah yang berkelanjutan di Provinsi Sumatera Utara.